Ethnobotany of medicinal plants in the Dayak Linoh Tribe in Sintang District, Indonesia - HENDRIKUS JULUNG; MARKUS IYUS SUPIANDI; BENEDIKTUS EGE; SITI ZUBAIDAH; SUSRIYATI MAHANAL (Society for Indonesian Biodiversity, 2023)
Abstract. Julung H, Supiandi MI, Ege B, Zubaidah S, Mahanal S. 2023. Ethnobotany of medicinal plants in the Dayak Linoh Tribe in Sintang District, Indonesia. Biodiversitas 24: 767-775. The Linoh Dayak people have long used medicinal plants to deal with health problems in their community. However, along with the advancement of science, the influx of foreign cultures and the degradation of nature and the environment, traditional knowledge about medicinal plants is only owned by the older generation, and the transmission of information is limited by word of mouth and not well documented. This study aimed to document various medicinal plants used by the Dayak Linoh people. The research used a qualitative approach using field surveys. Informants were selected using the purposive sampling method. The informants interviewed consisted of customary leaders (key informants), village heads (main informants), and recommended informants, such as traditional birth attendants (village midwives), hamlet heads, and community members who know medicinal plants. Medicinal plant data were obtained through in-depth interviews, participatory observation, and documentation related to the local names of the plants, the parts used, and how to manage and use them. Data analysis was carried out in a qualitative descriptive manner. The results showed that 55 species of medicinal plants consisting of 34 plant families were used by the Dayak Linoh tribe. The most widely used part of the plant is the leaf (39, 71%). People in the community boiled the leaves and drank the extract. The most used families in the three tribal communities of the Dayak Linoh tribe, were Zingiberaceae (9 species) and Myrtaceae (3 species). The plant parts used by the Dayak Linoh tribe were root, tuber, rhizome, stem, bark, banana heart, fruit, fruit skin, leaf, and seed. The Dayak Linoh tribe used medicinal plants to treat boil (7 plants) and for postpartum stamina recovery (7 plants). The communities processed and used the medicinal herbs conventionally by boiling and drinking.